Severity of atopic dermatitis is associated with gut-derived metabolites and leaky gut-related biomarkers - Leszek Blicharz; Emilia Samborowska; Radosław Zagożdżon; Iwona Bukowska-Ośko; Joanna Czuwara; Michał Zych; Aleksander Roszczyk; Karol Perlejewski; Karolina Makowska; Joanna Nowaczyk; Michał Zaremba; Karolina Kazimierska; et al. (Scientific Reports)
Abstract Dysbiosis of the gut microbiota may contribute to metabolic dysregulation, intestinal barrier disruption, and inflammatory disorders. The objective was to identify gut-derived metabolites and leaky gut biomarkers linked to atopic dermatitis. Fifty adult patients with atopic dermatitis and 25 controls were studied. Blood levels of 30 biomarkers were analyzed using liquid chromatography-mass spectrometry, ELISA, and Luminex assays, and correlated with clinical outcomes (EASI, SCORAD, extent of skin lesions). We discovered higher concentrations of caproic acid, glycerophosphocholine, Reg3A, I-FABP, IL-10, and IL-22 in patients with atopic dermatitis compared to controls, while the concentration of trimethylamine was lower. Disease severity was associated with lower caproic acid and isocaproic acid levels. Indoxyl and leaky gut biomarkers (LBP, Reg3A, IL-10, IL-22) correlated with higher disease activity. Leaky gut-related biomarkers were positively associated with C6 short-chain fatty acids and negatively with indoxyl. These findings highlight potential biomarkers of the gut-skin axis that could aid in predicting the onset and evolution of atopic dermatitis. Given that short-chain fatty acids and indoxyl are fermentation products of fiber and protein, respectively, our results suggest that a fiber-rich diet and moderation of protein intake could be beneficial not only for metabolic health but also in managing atopic dermatitis.